Intention to start a business and entrepreneurship education programme: a pre- and post-programme research design. Issue 4 (1st July 2020) - Çera, Gentjan; Çera, Edmond
Abstract : Purpose: The effect of a study programme in entrepreneurship on intention to start a business has not received adequate attention by researchers using a pre- and post-programme research design. The purpose of this paper is to find evidence of entrepreneurship education programme on entrepreneurial intention in the context of a post-communist transition county. Design/methodology/approach: Coarsened exact matching method is performed to achieve two similar groups: control (people who did not attend a study programme in entrepreneurship) and treated (those who attended) groups. Based on a set of covariates as identified in theory, 442 out of 528 members were matched. Hypotheses developed in a pre- and post-programme setting can be tested by using the ANCOVA. Members' scores on intention to start a business before the programme was introduced were used as the covariate in this analysis (pre-programme). Findings: The analysis confirms a significant difference between the two groups on entrepreneurial intention after the study programme in entrepreneurship was completed (post-programme). The results suggest that entrepreneurial intention is affected by entrepreneurship education programme. Research limitations/implications: This study offers useful insights for universities and individuals running a business. Aiming better results in terms of entrepreneurship, university, industry and government should align their efforts following a triple helix model. Originality/value: This work adds value to the entrepreneurship literature in the context of post-communist transition country. Furthermore, it uses a rigour methodology that makes the comparison of control and treated groups possible.